Evaluation of miR-216a and miR-217 as Potential Biomarkers of Acute Exocrine Pancreatic Toxicity in Rats. (February 2017) - Wang, Jianying; Huang, Wenhu; Thibault, Stephane; Brown, Thomas P.; Bobrowski, Walter; Gukasyan, Hovhannes J.; Evering, Winston; Hu, Wenyue; John-Baptiste, Annette; Vitsky, Allison
Detecting and monitoring exocrine pancreatic damage during nonclinical and clinical testing is challenging because classical biomarkers amylase and lipase have limited sensitivity and specificity. Novel biomarkers for drug-induced pancreatic injury are needed to improve safety assessment and reduce late-stage attrition rates. In a series of studies, miR-216a and miR-217 were evaluated as potential biomarkers of acute exocrine pancreatic toxicity in rats. Our results revealed that miR-216a and miR-217 were almost exclusively expressed in rat pancreas and that circulating miR-216a and miR-217 were significantly increased in rats following administration of established exocrine pancreatic toxicants caerulein (CL) and 1-cyano-2-hydroxy-3-butene (CHB) as well as in rats administered a proprietary molecule known to primarily affect the exocrine pancreas. Conversely, neither microRNA was increased in rats administered a proprietary molecule known to cause a lesion at the pancreatic endocrine–exocrine interface (EEI) or in rats administered an established renal toxicant. Compared with amylase and lipase, increases in miR-216a and miR-217 were of greater magnitude, persisted longer, and/or correlated better with microscopic findings within the exocrine pancreas. Our findings demonstrate that in rats, miR-216a and miR-217 are sensitive and specific biomarkers of acute exocrine pancreatic toxicity that may add value to the measurement of classical pancreatic biomarkers.